The UN Sustainable Development Goals; using WHO ‘Health Promoting Schools’ to create change. - Macnab, Andrew John; Mukisa, Ronald (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Not required for photo essay